2022
DOI: 10.3389/fpsyt.2022.976544
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for the treatment of subthreshold bipolar disorders: Targeted high dose levothyroxine and repetitive transcranial magnetic stimulation for mitochondrial treatment

Abstract: Bipolar spectrum disorder includes Bipolar I, Bipolar II and subthreshold bipolar disorders (BD). The condition is highly prevalent, disabling and associated with high mortality. Failure of diagnosis is high. Subthreshold presentations present as 4 or more changes in polarity, are generally less responsive to standard treatment and as a result, drug combinations are often needed. High Dose Levothyroxine (HDT) has been reported to be safe and effective with this condition. Treatment response has been associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…We do, however, argue that the presence of a DiO1 variant might play a greater role in protecting the periphery from the effects of high-dose levothyroxine, which has been shown in many studies [16], including the cohorts treated by the authors [18,19]. These mutations explain the disease model and mitochondrial dysfunction, as well as the model the authors published for the disease [26].…”
Section: Discussionmentioning
confidence: 80%
“…We do, however, argue that the presence of a DiO1 variant might play a greater role in protecting the periphery from the effects of high-dose levothyroxine, which has been shown in many studies [16], including the cohorts treated by the authors [18,19]. These mutations explain the disease model and mitochondrial dysfunction, as well as the model the authors published for the disease [26].…”
Section: Discussionmentioning
confidence: 80%
“…[93,94]. What's more, supraphysiological doses of TH also appeared to be an excellent option for BD treatment [95,96]. The reason maybe that BD has mitochondrial dysfunction and low ATP cellular state, while the uptake of TH in the cell is energy dependent.…”
Section: Treatment Of Bdmentioning
confidence: 99%
“…Neuroplasticity can be induced by both rTMS (Lenz et al, 2016) and tDCS (Ranieri et al, 2012), and we recently found evidence of increased neuroplastic changes in the rat brain after a single treatment of TILS (Wade et al, 2023). The induction of neuroplasticity by these methodologies may be one key mechanism by which they have a therapeutic effect in bipolar disorder (Zamar et al, 2022;D'Urso et al, 2023). rTMS, tDCS, and TILS also show promise in treating age-related cognitive decline (Vargas et al, 2017;Cai et al, 2019;Phipps et al, 2021).…”
Section: Comparison Of Tils With Non-invasive Magnetic and Electrical...mentioning
confidence: 99%